Paradigm and Philosophical Foundation of Qualitative Research - Norlaila, Norlaila; Huda, Nuril (The Future of Education Journal, 2026)
Qualitative research has methodological and epistemological characteristics that fundamentally distinguish it from quantitative approaches, particularly in understanding complex, dynamic, and meaningful social realities. This article aims to comprehensively analyze the paradigm and philosophical foundations underlying qualitative research, with an emphasis on its ontological, epistemological, and axiological dimensions. The research employs a literature review method by examining various scientific sources, including research methodology textbooks, national and international journals, and works related to the philosophy of science. The analysis technique used is content analysis to identify and synthesize key concepts related to the qualitative research paradigm. The results show that qualitative research is rooted in interpretive and constructivist paradigms, which view reality as plural, subjective, and constructed through social interactions and human experiences. From an epistemological perspective, knowledge is understood as the result of an interactive relationship between the researcher and the research subject, positioning the researcher as the primary instrument in the research process. Meanwhile, from an axiological perspective, qualitative research acknowledges the role of values, ethics, and the reflexivity of the researcher throughout the research process. This study is expected to strengthen the conceptual and philosophical understanding of researchers in designing and conducting qualitative research in a scientific, reflective, and responsible manner.